0335 Frontal Expression of NREM Sleep Oscillations are Associated with Executive Function in Children and Adolescents. (27th May 2020) - Lui, K K; Mander, B A; Radom-Aizik, S; Chappel-Farley, M G; Dave, A; Chen, I Y; Benca, R M; Neikrug, A B
Abstract: Introduction: The prefrontal cortex, an area known for executive functioning (including inhibition and self-monitoring) develops during childhood and adolescents, with a pattern of posterior to anterior brain development. Slow-wave activity (SWA) in NREM sleep, tracks brain development with high SWA power migrating from occipital to frontal region as brain maturation occurs. This pilot study aimed to examine whether slow wave topography is correlated with executive function in youth. Methods: Seventeen healthy children and adolescents (ages 11-17; 10 females) underwent overnight polysomnography (PSG) with high-density electroencephalography (hdEEG). Behavior Rating Inventory of Executive Function (BRIEF) was administered to assess executive function. SWA (SWA1: 0.5-1 Hz; SWA2: 1-4.5 Hz) and spindle (slow sigma: 11-13 Hz; fast sigma: 13-16 Hz) activity was analyzed with spectral analysis using Welch's method. BRIEF subscales of inhibition and monitor were correlated with SWA and sigma power across all derivations, with Holm-Bonferroni correction (126 channels). Significant derivations were then controlled for sex and self-reported Tanner stage using multiple regression Results: BRIEF-Inhibition scale (i.e., ability to repress impulsivity) and SWA1 in anterior frontal derivations were negatively correlated (R 2 =0.58, p=0.047 corrected). BRIEF-Monitor scale (i.e., self-perception of one's own behavior and interpersonal awareness) was negatively correlated with fast sigma in anterior frontal derivations (R 2 =0.65, p=0.013 corrected). These associations were significant after controlling for sex and Tanner stage. Conclusion: These results support the hypothesis that NREM sleep oscillations are associated with executive function and reflect changes in neuroplasticity related to "back-to-front" brain maturation. Future longitudinal studies should combine multi-modal neuroimaging of brain structure and local sleep with comprehensive assessments of executive function to evaluate the possible link between local sleep and development of higher-order cognition in frontal brain regions in youth. Support: NCATS grant #UL1TR001414 & PERC Systems Biology Fund